Abundance and distribution of microplastics in surface waters of the Kattegat/ Skagerrak (Denmark) - Gunaalan, K.; Almeda, R.; Lorenz, C.; Vianello, A.; Iordachescu, L.; Papacharalampos, K.; Rohde Kiar, C.; Vollersten, J.; Nielsen, T.G. (Elsevier, 2022)
Microplastics (MPs) are ubiquitous pollutants in the ocean, and there is a general concern about their persistence and potential effects on marine ecosystems. We still know little about the smaller size-fraction of marine MPs (MPs <300 μm), which are not collected with standard nets for MPs monitoring (e.g., Manta net). This study aims to determine the concentration, composition, and size distribution of MPs down to 10 μm in the Kattegat/Ska gerrak area. Surface water samples were collected at fourteen stations using a plastic-free pump-filter device (UFO sampler) in October 2020. The samples were treated with an enzymatic-oxidative method and analyzed using FPA-μFTIR imaging. MPs concentrations ranged between 11 and 87 MP m− 3 , with 88% of the MPs being smaller than 300 μm. The most abundant shape of MPs were fragments (56%), and polyester, polypropylene, and polyethylene were the dominant synthetic polymer types. The concentration of MPs shows a significant positive correlation to the seawater density. Furthermore, there was a tendency towards higher MPs concentrations in the Northern and the Southern parts of the study area. The concentration of MPs collected with the UFO sampler was several orders of magnitude higher than those commonly found in samples collected with the Manta net due to the dominance of MP smaller size fractions. Despite the multiple potential sources of MPs in the study area, the level of MPs pollution in the surface waters was low compared (<100 MP m− 3 ) to other regions. The concen trations of MPs found in the studied surface waters were six orders of magnitude lower than those causing negative effects on pelagic organisms based on laboratory exposure studies, thus is not expected to cause any impact on the pelagic food web.
Keywords: Marine microplastics; FPA-μFTIR imaging; Basin scale; Polyester